ACCOUNTING CONSERVATISM DURING COVID-19: EVIDENCE FROM INDONESIA - Irwan Adimas Ganda Saputra; Maryam Bte Badrul Munir (Jurnal Aplikasi Akuntansi, 2023)
This study investigated the factors influencing accounting conservatism in the tourism sector during the Covid-19 pandemic. The sample was selected through purposeful sampling and assessed through multiple linear regression. The investigation results showed that leverage significantly impacts accounting conservatism, while business size has a significant negative impact. Neither institutional ownership nor capital institutions significantly impacted accounting conservatism during the COVID-19 pandemic. The study also discovered that firms with a higher level of accounting conservatism were better able to control the impact of the pandemic on their financial performance and maintain their firm's financial performance despite challenging economic conditions than firms with a lower level of conservatism. This proved how accounting conservatism contributes in improving how the pandemic's effects are reflected in financial reporting. Overall, the results of this Indonesian study indicated that conservatism in accounting has been a valuable tool for businesses to control the COVID-19 pandemic's effects on their financial accounts. Thus, by recognizing losses and expenses earlier, companies could provide a more accurate picture of their financial position and better manage the risks associated with the pandemic.